Enhanced Cycling Ability of V2O5 Aerogel using Room‐Temperature Ionic Liquid‐Based Electrolytes. Issue 7 (27th April 2016) - Moretti, Arianna; Jeong, Sangsik; Passerini, Stefano
Abstract: Vanadium oxide is an attractive high‐capacity cathode material for metal batteries, but it is affected by severe capacity fading upon cycling in conventional electrolytes. In this manuscript, it is shown that the cycling ability of vanadium oxide (V2 O5 ) aerogel cathodes can be substantially improved by using properly designed electrolytes. In particular, the electrochemical characterization of V2 O5 aerogel, in combination with room‐temperature ionic liquid‐based electrolytes, demonstrates cycling stabilities above 600 cycles with capacity retentions higher than 80 %. Furthermore, the ionic liquid‐based electrolytes grant cyclability and safety in lithium–metal batteries even above room temperature. Abstract : The best match : The electrochemical behavior of V2 O5 aerogel in combination with room‐temperature ionic liquid‐based electrolytes is investigated. The outcome evidences a great improvement of the cycle life of the aerogel and the feasibility of safer Li–metal batteries.